Unorganized Religion: Pentecostalism and Secularization in Denmark, 1907-1924 - Christensen, Nikolaj, (Global Pentecostal and Charismatic Studies ;, 2022)
Two phenomena profoundly changed the shape of Christendom in the twentieth century: the rise of secularism in Europe, and the rise of Pentecostalism elsewhere. This book investigates the impact of an emerging secular culture on the early Pentecostal movement, using previously unpublished data to build its case study on Denmark. The first Pentecostals were idealists who sought to influence the existing churches from within, but eventually this approach gave way to the more successful strategy of forming separate Pentecostal churches. The insights found herein apply to all religious minorities who seek to adapt to an inhospitable context.